International and European experience of avoiding corruption risks during public procurement - Altsyvanovych, O. V.; Tsymbalenko, Y. Y. (Aspekty publichnoho upravlinni͡a, 2018)
The international and European experience of avoiding corruption risks in public procurement has been investigated. An analysis of the functioning of the public procurement system in various countries led to the conclusion that the authorized authorities use various mechanisms to ensure the effectiveness of its organization. This applies, in particular, to the requirements for competitive bidding, disclosure of information by their participants, establishing the responsibility of officials for compliance with the procedures and rules established by law, etc.Along with the regulatory documents governing the procurement procedure in foreign countries directly, the important role is played by declarations and standards relating to the direct regulation of the procedures and principles of public finance FC.The main approaches used in international practice to avoid corruption risks in the implementation of public procurement are identified, namely: psychological methods, technical methods, regulation of processes, repressive means.It was concluded that, limited to individual branches of influence or the methods indicated above, only a short-term effect can be obtained, because after a certain period of time, the structure and mechanism for releasing illegal income will change, moving into industries not covered by instruments of control and opposition. As a result, the total corruption losses will return to their previous size or even exceed them. Consequently, it is possible to get tangible results of indicators of reducing corruption only by applying an integrated approach, that is, a balanced use of all methods of counteraction at each stage of the public procurement process.